Influence of increasing niacin on growth performance and carcass characteristics of grow-finish pigs reared in a commercial environment - Real, D.E.; Alonso, E.; Nelssen, Jim L.; Unruh, John A.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
There were 1,243 growing pigs used to determine the effects of increasing dietary niacin on growth performance and meat quality of pigs reared in a commercial environment. The dietary treatments consisted of a control diet (no added niacin) or the control diet with 12.5, 25, 50, 100, or 500 g/ton of added niacin. Increasing dietary niacin decreased ADFI and improved F:G for the overall study. Increasing dietary niacin improved carcass shrink, ultimate pH, drip loss percentage, and loin color. Increasing dietary niacin up to 50 ppm improved feed efficiency, but higher concentrations (up to 50 ppm) decreased carcass shrink, and improved muscle quality in grow-finish pigs.
Keywords: Niacin; Swine; Finishing pigs; Pork quality